Faktor Kurangnya Minat Siswa MI Terhadap Mata Pelajaran Sejarah Kebudayaan Islam - Munawwir; Hendra, Rafika Salsa Nur; Zahroh, Tsalitsa Lathivatuz (Ikatan Dai Indonesia, 2024)
The subject of Islamic Cultural History (SKI) at Madrasah Ibtidaiyah is a subject that is quite difficult to understand compared to other sciences, because SKI studies something that has happened but has not directly experienced the event from students. The purpose of this study was to describe students' interest in studying SKI subjects, whether there was a relationship between interest in learning and the learning outcomes of SKI subjects in the class concerned, and how strong the relationship between student interest and learning was. Results The form of this research is a qualitative type of literature study. The results of a study conducted on MI students showed that because the SKI subject is an Islamic cultural history lesson that students as Muslims must know, students' interest in SKI subjects again needs to be considered and increased. Interest in learning has a positive and significant relationship with student learning outcomes in SKI subjects.